Anatomical plasticity of Pinus taeda L. needles in the sun and shade of the mountainous region of Santa Catarina (Research, Society and Development, 2024)
The growth and development of conifers are related to the capacity for photosynthesis and gas exchange in their persistent leaves (needles), as well as related to the long-term availability of irradiance in gradients across the canopy. The objective of the present research was to describe the morphophysiological variations and compare the phenotypic plasticity of Pinus taeda L. leaves under sun and shade in cultivation in the mountainous region of Santa Catarina. leaves under sun and shade in cultivation in the mountainous region of Santa Catarina. Leaves were collected from five plants under sun and shade conditions. Histological analyzes of leaf measurements were performed using light microscopy. For each morphometric characteristic, the phenotypic plasticity index was calculated. In sun leaves, the thickness of the epidermis on the adaxial surface was smaller, while the area of ​​the central cylinder, the area of ​​the phloem and the resinous ducts were larger. The central cylinder presented the highest phenotypic plasticity index (0.40), followed by the epidermis on the adaxial surface (0.28), the phloem (0.27) and the resinous duct (0.25). The lowest plasticity indices were recorded for the chlorophyll parenchyma on the adaxial side (0.03) and for the epidermis on the abaxial side (0.03). The results indicate that light promotes structural changes in P. taeda leaves related to the mechanisms of reception of direct sunlight (adaxial face) and the conduction of synthesis products through the plant (area of the central cylinder, phloem and resinous ducts).